KAJIAN KEBERLANJUTAN USAHATANI KELAPA DALAM DI SEKITAR CAGAR ALAM HUTAN BAKAU PANTAI TIMUR KABUPATEN TANJUNG JABUNG TIMUR - Faried; Murdy, Saad; Hamid, Ernawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
Coconut farming in the East Tanjung Jabung Regency, especially around the East Coast Mangrove Forest Nature Reserve has links to one another. This research aims to 1) Describe the deep coconut farming.2) Analyze the income of the deep coconut farming. 3) Analyzing the sustainability status of coconut farming in the vicinity of the East Coast Mangrove Forest Nature Reserve Tanjung Jabung Timur Regency from the ecological, economic and social dimensions. This research was conducted in four sub-districts around the Mangrove Forest East Coast Nature Reserve namely Mendahara District, Kuala Jambi District, Muara Sabak Timur District and Nipah Panjang District in July to September 2019. Coconut farming income for each farmer around the East Coast Mangrove Forest Reserve Rp. 2,676,011 / month is greater than UMR Jambi Province in 2019, the income of coconut farming in having an economically sustainable. The level of sustainability of coconut farming in which is based on a multidimensional sustainability index shows a fairly sustainable value with a value of 52.01. Based on that, it can be said that the coconut farming in the vicinity of the East Coast Mangrove Forest Nature Reserve is quite sustainable, where in terms of ecology, economy and social benefits for the community and does not cause harm to the environment. The most prominent or sensitive attribute to the sustainability of the ecological dimension is the cropping pattern and crop rejuvenation, the economic dimension is the development of coconut prices and the availability of inputs at the local level, for social dimensions, namely how to open land and community social activities.